2021
DOI: 10.1177/10547738211017688
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Web-Based Communication between a Nurse and a Family Member on the Perceived Stress of the Family Member of Patients with Suspected or Confirmed COVID-19: A Parallel Randomized Clinical Trial

Abstract: The aim of this study was to identify the effect of web-based communication between a nurse and a family member of a patient with COVID-19 on his/her perceived stress. In this multicenter parallel randomized controlled trial, 67 family members of COVID-19 patients admitted to the Intensive Care Unit (ICU) were investigated. In the intervention group, web-based communication was performed for four consecutive days for 10 to 15 minutes. The Perceived Stress Scale (PSS-14) were completed in both groups before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a large French multicentre study (Azoulay et al, 2022), the family members of COVID‐19 patients reported more intense feelings of isolation during the ICU stay and compared to family caregivers of other patients, the risk of developing stress symptoms in the months after ICU admission was twice as high. Web‐based communication has been found in other studies to be associated with reduced post‐traumatic stress symptoms experienced by family members (Shariati et al, 2021), improved patient recovery and increased healthcare professional morale during the COVID‐19 pandemic (Rose et al, 2021). Even though personal contacts were preferred by the family members in the current study, the telephone or video calls were highly valued.…”
Section: Discussionmentioning
confidence: 90%
“…In a large French multicentre study (Azoulay et al, 2022), the family members of COVID‐19 patients reported more intense feelings of isolation during the ICU stay and compared to family caregivers of other patients, the risk of developing stress symptoms in the months after ICU admission was twice as high. Web‐based communication has been found in other studies to be associated with reduced post‐traumatic stress symptoms experienced by family members (Shariati et al, 2021), improved patient recovery and increased healthcare professional morale during the COVID‐19 pandemic (Rose et al, 2021). Even though personal contacts were preferred by the family members in the current study, the telephone or video calls were highly valued.…”
Section: Discussionmentioning
confidence: 90%
“…In a study by Cohen et al, Cronbach's alpha of the PSS-14 version was reported as 0.86 (19). In studies conducted in Iran, Cronbach's alpha coefficient obtained from this questionnaire has been reported as 0.89 (21). Maroufizadeh et al indicated that the Persian version of the PSS-10 was positively correlated with the Depression Anxiety Stress Scales (DASS-21) and its subscales and an acceptable convergent validity in adults with asthma (22).…”
Section: Methodsmentioning
confidence: 88%
“…Items 4, 5, 6, 7, 9, 10, and 13 were reverse-coded before analysis (never = 4 and very often = 0). A higher score indicates more perceived stress (19)(20)(21). In a study by Cohen et al, Cronbach's alpha of the PSS-14 version was reported as 0.86 (19).…”
Section: Methodsmentioning
confidence: 99%
“…The DASS-21 is a standard scale whose options are scored from 0 to 3. In this tool, seven items related to stress symptoms (2,6,8,11,12,14,18), seven items related to anxiety symptoms (1,4,7,7,15,19,20), and seven items related to depression symptoms (3,5,10,13,16,17,21). Scores 0-4 are mild, 5-11 are moderate, and more than 12 indicate severe psychological symptoms.…”
Section: Depression Anxiety and Stress Scale-21mentioning
confidence: 99%
“…Care is individualized because of the different severities of COVID-19 and the importance of factors such as safety, limit distance between clinical staff and family near the patient within the hospitals for example. On the other hand, even though about a long time has passed since the COVID-19 pandemic started, a limited number of studies have been conducted to evaluate the psychological and dimensions of care of family caregivers of patients with COVID-19 [18][19][20] and most studies have focused on caring problems in health workers like nurses and hospital caregivers. Therefore, the current study investigated the predictor factors of care burden in family caregivers of patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%